Manejo inicial del accidente cerebrovascular (ACV) isquémico agudo. Los detalles hacen la diferencia - Illanes D., Sergio; Díaz T., Violeta (Revista Hospital Clínico Universidad de Chile, 2008)
The cerebrovascular disease, especially the ischemic stroke, is the second cause of death in our country. In Chile every year we have 14.000 new cases of ischemic stroke; this number is going up due to the progressive aging of our population. Every action we do during the six first ours of the evolution of the disease are critical for the final outcome. A proper treatment is made of a group of unspecific actions that can really change the prognosis of the disease: Multidisciplinary approach, quick stabilization, unspecific neuroprotection, CT in the emergency room and hospitalization in a Stroke Unit, prevent and treat infections, early physical therapy, diagnosis of underlying disease and secondary prevention. The current law in Chile guarantee to every patient with an ischemic stroke the right to be hospitalized under the suspect of a stroke and to be followed up by a Neurologist, Psychologist, Physiatrists, kinesiologist, Speech and swelling therapist and a physical therapist. This law can only be fulfilled if every hospital in our country, or at least one per region, has its own Stroke Unit.